Cognitive Evaluation of Cochlear Implanted Adults Using CODEX and MoCA Screening Tests. Issue 8 (September 2017) - Ambert-Dahan, Emmanuèle; Routier, Shirley; Marot, Lucie; Bouccara, Didier; Sterkers, Olivier; Ferrary, Evelyne; Mosnier, Isabelle
Abstract : Objective: The relationship between hearing loss and cognitive function has already been established. The objective of our study was to determine whether the two short cognitive tests, COgnitive Disorders EXamination (CODEX) and Montreal Cognitive Assessment (MoCA), could be used in daily clinical practice to detect cognitive impairment, and its changes after cochlear implantation. Patients: Eighteen patients with severe to profound postlingual progressive hearing loss (mean age ± SEM: 64 ± 3.5 yr; range, 23–83 yr) were tested before, and 12 months after cochlear implantation, with adapted visual presentation of CODEX and MoCA tests. Auditory performance was tested under best-aided conditions in quiet and noise. Results: Twelve months after cochlear implantation, hearing performance had clearly improved (paired t tests, p  < 0.05). In addition, among the eight patients who had an abnormal cognitive score before implantation, four improved their cognitive performance, and were thus considered to be normal. No major alteration of cognitive performance was observed in the 10 patients who had normal cognitive performance before implantation. Conclusion: CODEX and MoCA are rapid tests that could be considered to be relevant cognitive performance screening tests. They could be used in daily clinical practice to improve the multidisciplinary sensory-cognitive monitoring of the elderly population.